EVALUATION OF POLYMORPHONUCLEAR IMMUNE CELLS IN BIOCOMPATIBILITY TEST DFLP SPONGE CARTILAGE SCAFFOLD, ADIPOSE-DERIVED MSC AND SECRETOME WITH CARTILAGE INJECTION MODEL - Brilliant Citra Wirashada; Dwikora Novemberi Utomo; Lukas Widhiyanto (Journal Orthopaedi and Traumatology Surabaya)
Background: In recent years, Freeze-Dried Scaffold Bovine Cartilage has been widely used as an alternative therapy for joint cartilage defects. This study aims to determine the biocompatibility of scaffold without involving implantation which provides clinical reports as expected through the evaluation of post-implantation chondrocytes regeneration, biocompatibility markers of the scaffold, and biocompatibility of sponge cartilage scaffold involving cartilage defects New Zealand White Rabbit.